OPTIMALISASI MANAJEMEN KEUANGAN SEDERHANA BAGI LITERASI UMKM - Nurbaiti, Nurbaiti; Putri, Nadia Tiara; Sejati, Hiro; Dafitri, Rizkika; Suryani, Suryani; Nahadia, Risna; Mustofa, Mustofa; Pangestu, Herwindu Danu; Wulandari, Friska Tri (Jurnal Bakti Masyarakat Manajemen, 2023)
This research is motivated by the results of community service observations that focus on the problem of managing UMKM  finances. To realize this, this study aims to enable UMKM actors to be able to run and maintain their businesses well under any circumstances and can optimize the financial management of UMKM. The research was conducted by a group of economics and management students of Malahayati University.  With the research method, the results show that students get experience because they are directly involved in UMKM. With this activity, students can learn how to manage finances well and effectively, and can be more familiar with the use of technology and simple financial applications that can help facilitate business financial management.